Parental Involvement in Islamic Education: A Literature Review and Its Implications for Students - Alfiyanto, Afif; Ikhwan, M.; Mahdi, Mahdi; Gumilang, Randi Muhammad; Wahyudi, M. Agus (Sekolah Tinggi Ilmu Syariah Ummul Ayman Pidie Jaya, 2024)
This study aims to explore the role and form of parental involvement in Islamic education and its implications for student development. Using a qualitative approach and literature review method, this study examines primary sources such as the Qur'an, Hadith, and the words of scholars related to Islamic education, followed by an analysis of relevant previous research. This study not only explores the values contained in religious sources, but also compares empirical findings from previous studies that identify various forms of parental involvement in supporting children's education, such as emotional support, participation in school activities, and communication with teachers. The results of the study show that parental involvement is strongly emphasized in Islamic teachings, with an emphasis on the development of children's character and morals. Various forms of parental involvement contribute significantly to the improvement of academic achievement and character development of students. The implications of this involvement show that students who have active parents tend to show better learning outcomes and have strong moral and spiritual values. This study recommends the development of training programs for parents and activities that can directly involve them in Islamic education. Thus, this study emphasizes the importance of the role of parents in forming a generation that is not only academically superior, but also has good morals and strong spiritual values.